Effect of Reynolds and Prandtl Numbers on Mixed Convection in an Obstructed Vented Cavity - Rahman, M. M.; Billah, M. M.; Alim, M. A. (Journal of Scientific Research, 2011)
A numerical investigation is conducted to analyze the steady flow and thermal fields as well as heat transfer characteristics in a vented square cavity with a built-in heat conducting horizontal solid circular obstruction. Hydrodynamic behavior, thermal characteristics and heat transfer results are obtained by solving the couple of Navier-Stokes and energy equations by using a weighted residuals Finite element method. The computation was made for different Reynolds number, Prandtl number ranging from 50 to 200 and from 0.71 to 7.1 at the three different convective regimes. Three different regimes are observed with increasing Ri: forced convection (with negligible free convection), mixed convection (comparable free and forced convection) and free convection dominated region (with higher free convection). The results are presented to show the effects of the Reynolds number, Prandtl number on flow pattern, thermal field and heat transfer characteristics at the three convective regimes. It is found that the flow and thermal field strongly depend on the Reynolds number, Prandtl number as well as Richardson number. As the Reynolds number and Prandtl number increase, the heat transfer rate increases but average fluid temperature in the cavity and temperature at the cylinder center decrease at the three convective regimes. Keywords: Mixed convection; Finite element method; Obstructed vented cavity; Prandtl number. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.4344 J. Sci. Res. 3 (2), 271-281 (2011)